Effect of abhrak bhasma and silicon dioxide on hepatic and renal glutathione status in rats: hepatoprotection testing against single dose carbon tetrachloride induced hepatotoxicity - Teli, Parashuram; Jadhav, Jaywant; Kanase, Aruna (International Journal of Pharmacology and Toxicology, 2014)
Background: Glutathione (GSH) is an important intracellular antioxidant. Intrahepatic GSH levels are depleted in liver diseases. Objectives: In present study, effect of abhrak bhasma (an Ayurvedic drug) and silicon dioxide (SiO2) on hepatic and renal GSH status against CCl4 intoxicated male albino rats were investigated. Methods: Single dose of CCl4 (3.0ml/kg body wt, sc) was used to induce hepatotoxicity. Graded doses (10, 20, 30 and 40mg/ kg body wt) of abhrak bhasma and SiO2 were concurrently given with CCl4. Hepatic and renal GSH content was studied after 24 hrs. Results: Results showed that rats exposed to CCl4 exhibited decreased GSH in liver. It was counteracted and maintained to normal levels by the treatment of abhrak bhasma (minimum protective dose-10mg). SiO2 treatments did not affect GSH activity in liver significantly. Single dose of CCl4 had not influenced GSH content in kidney alone or with any of the doses of abhrak bhasma or SiO2. Conclusion: CCl4 single dose depletes GSH content significantly in liver but not in kidney. These results suggest that single dose treatment of abhrak bhasma (10mg onwards) protects GSH content and thus manages CCl4 induced free radical generation scavenging them. Keywords: Abhrak Bhasma, Antioxidant, Glutathione, Hepatotoxicity, Silicon Dioxide.